Metaverse Security Challenges and Solutions: A Comprehensive Analysis of Contemporary Technologies - Rahimi, Nasrallah; Hakimi, Musawer; Rahmani, Khoshal; Rastagari, Mohammad Aziz; Danish, Jawad; Shahbazi, Hafizullah (Transpublika Publisher, 2025)
The metaverse, the virtual world integrating augmented reality, virtual reality, and other digital technologies, poses tremendous opportunities and challenges regarding security, privacy, and governance. With digital worlds such as the metaverse beginning to take place, user-generated content and user interaction are proving to be more and more a daunting task. In this paper, the metaverse security challenge is discussed and some proposals and recommendations are formulated. This study used a mixed-methods approach and surveyed data from 85 students, lecturers, and technical professionals who were interested in information technology. Quantitative data were captured through structured questionnaires and surveys, and processed in SPSS, and qualitative data were elicited through thematic analysis. The results suggest strong support for the metaverse, yet raise concerns for technical limitations, privacy issues and environmental impacts. Technical problems like hardware requirements and system lag were discovered by 50% of the respondents to be significant barriers, 12% mentioned privacy and security concerns as barriers, and 7% reported other types of barriers such as access issues. Most respondents were concerned that the metaverse was not very safe but reported areas for improvement. The study advises stricter regulation, better legislation on data privacy, and a better reporting mechanism to combat online abuse. Therefore, the work adds to a new metaverse security literature and provides applied policy, governance, and space-building lessons. With the expansion and further development of the metaverse, future research will be required to deconstruct these dimensions more extensively.